Innovation of eco-friendly TiO2 nano catalyst for new pyrimidine carbonitiriles candidates, assessed for significant antioxidant activity, anti-inflammatory effects, and by insilico studies - Wesam S. Shehab; Ahmed F. EL-Farargy; Abdel Rahman B. A. El-Gazzar; Hend A. Haikal; Samar M. Mouneir; Abdul-Hamid M. Emwas; Mariusz Jaremko; Magda H. Abdellattif (PLoS ONE, 2025)
Production of titanium dioxide nanoparticles (TiO2- NPs) is carried out in high quantities for an extensive range of applications. These nanoparticles have various physicochemical properties, which can affect their bioactivity. The Biginelli synthesis of 4-cyanobenzaldehyde, ethyl cyanoacetate, and thiourea in the presence of TiO2 nanoparticle yields 4-(4-cyanophenyl)-6-oxo-2-thioxohexahydropyrimidine-5-carbonitrile (1). This multi-component system is safe, eco-friendly, and non-toxic. The introduction of the new system saves time and reduces chemical usage. Compound (1) underwent reactions with various additional compounds such as (methyl iodide, chloroacetonitrile, chloroacetone, acrylonitrile, ethyl chloroacetate, and chloroacetic acid/benzaldehyde). The newly synthesized compounds possess remarkable anti-inflammatory and antioxidant activities, making them an excellent choice for therapeutic use.. The in-silico studies include molecular docking using MOE, Pharmacokinetics using Toxoradar, SAR, and DFT studies.